Electrochemical investigation and thermodynamic assessment of the Mg-Pd system - Gierlotka W.; Terlicka S.; Gąsior W.; Dębski A.; Pęska M.; Polański M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This paper presents the results of electromotive force measurements using coulometric titration technique for liquid and solid Mg-Pd alloys with concentrations up to 0.70 Mg mole fraction and at 918 K. These measurements made it possible to verify the homogeneity range of the occurring phases and phase boundaries in the investigated system. Based on the obtained results and other thermodynamic data found in the literature, the phase diagram of the Mg-Pd system was optimized using the CALPHAD method and ab initio calculations. The thermodynamics of the intermetallic phases, the liquid phase, and the solid solutions were described by the correct equations, which can be used in the future to calculate multicomponent systems with the Mg-Pd system as one of the binary components. The thermodynamic calculations successfully reproduced the Mg-Pd phase diagram.